“Native” Religion in a Severn Ojibwe Community Voices From the Inside, Voices From the Outside - Valentine, Lisa Philips (Culture, 1992)
The actions and voices of the people of Lynx Lake tell a story of choosing to define themselves as Christians, and declare a long-standing, community-wide commitment to maintain a strong, unified Anglican profile. This study outlines the role of the church in Lynx Lake within its historical context, presents and analyses representative samples of Native-to-Native religious discourse including a sermon and several testimonials, and addresses changing religious views of younger members of the Severn community. Central to the study is a discussion of the use of a discourse-centered approach to ethnographic research.